PETIK LAUT: Social-Ideological Accommodation in the Fishermen Community of Kedungrejo Muncar Banyuwangi - Ainiyah, Nur (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2017)
This research aims to showing how accommodating the differences of two traditions ideologically and socially can create tolerance and peace in a plural society. The plurality of Muncar such ethnicity, religion, culture and class-economy could protect the conflict. They more choose the public interest than personal interest. The social reality of Muncar is showing with ritual Petik Laut which combines between Islamic and Osing tradition. Cosmologically both of them are different, Islam believes in the singular God and the Osing believes in the plural God. The main problem of this research is how the ideological and social accommodation between the Islamic and Osing tradition can work. So my conceptual framework of research that syncretism is the accommodation of differences which can create society to be peaceful. And the ritual collective is the combining media of how the differences because the ritual has the collective goal which is reached by society as the actors. This research shows that the differences of religion and ideology in the multi-ethnical and cultural society have potentials for conflict. But the conflict can be protected by involving the social agents of society like santri and kejawen in order to avoid riot. The ideological problem is significant and sensitive and it is easy to create raise strong emotions among the fishermen. The wrong interpretation of ideology can be fatal. However the coastal society generally is known as less temperamental and open-minded person and permissive for the religious and ideological plurality. Their attitudes which want to show ‘dignity’ (jati diri) are the characteristic of the coastal society. This attitude manifests in the petik laut ritual by involving the symbols of religions, cultures and ethnicities in Kedungrejo. The Kedungrejo society majority is Islam but they believe in Ratu Reja Mina as the fish Queen although it is the Osing belief. The honor for the Sayid Yusuf as the historical figure of the Petik Laut history is done together by them. These beliefs complete the Islamic belief for Prophet Hidir. The coastal cosmology of Kedungrejo is the result of accommodating between Islam and Osing. So it became the local ideology which can avoid the conflict. Because left one of two ideologies can create the ideological conflict in society. They are still doing the process for the survival society life peacefully although they have the different interpretation about ritual petik laut. The conflict of economy as the consequence of the work system between jaragan and pandiga, and the environmental conflict between fabric and society can assimilate in this ritual because the social function of petik laut can accommodate all of the elements of society even religion to include in this ritual. So the person who has the certain conflict became the ritual as the mediation for building up the social cohesion (silaturohmi) among the fishermen community, religious institution and the organization of the pesantren’s alumni. From the social accommodation, the social cohesion came back to unity so that peace can return to Kedungrejo.